Current and transimpedance mode instrumentation amplifier using a single new active component named CDTRA - Dikbas, Mehmet Cem; Ayten, Umut Engin (ELSEVIER GMBH, 2018)
In this study, both current and transimpedance mode instrumentation amplification operations are met through a new active building block proposal, namely Current DifferencingTransresistance Amplifier block, CDTRA. In order to regard CDTRA as an instrumentation amplifier (IA), two grounded passive resistors are needed. Passive resistors together with electronically tunable transresistance parameter of active block, r(m), set versatility over gain tunability for instrumentation amplifier. Proposed active block is current input, current/voltage output design. It has low impedance input, high impedance for current output, and low impedance for voltage output respectively. Since this particular IA is based on CDTRA, then it inherits these electrical characteristics fully. Numerous SPICE simulations are performed through the paper to verify validity of the study. TSMC 0.18 mu m CMOS technology parameters are utilized through simulations. Experimental work is performed for the proposed IA circuit.
Keywords: Instrumentation amplifier; Current differencing transresistance amplifier (CDTRA); Current mode; Transimpedance mode; Electronic tunability; Active component; HIGH CMRR; WIDE BANDWIDTH; VOLTAGE; DESIGN; Engineering; Telecommunications